PENGARUH TRANSFORMASI DIGITAL: KECERDASAN BUATAN DAN INTERNET OF THINGS TERHADAP PERAN DAN PRAKTIK AUDIT INTERNAL:SYSTEMATIC LITERATURE REVIEW - Hipolitus Hamonangan Rumahorbo; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
This research aims to determine the importance of implementing digital transformation: Artificial intelligence (AI) and the Internet of Things (IoT) in internal audit systems to conduct internal controls and investigate document the differences found in empirical research. The research is conducted by collecting 20 articles from Scopus published between 2020 until 2023, which will be classified based on the methods used and research results. The method employed in this research is Systematic Literature Review (SLR), which is used to examine the outcome, methodologies, topics/themes, recommendations, and limitations of the published articles. The analysis results provide evidence that digital transformation: Artificial intelligence (AI) and the Internet of Things (IoT) in internal audit systems have a positive impact on internal audit practices within each company or organization. However, it is important to consider the potential risks and challenges associated with their implementation. AI and IoT are innovative business technologies in digital transformation aimed at managing and transforming businesses. Digital Transformation not only involves technological influences but also changes in culture, operations, and business models